Interpreting IGF-1 in children treated with recombinant growth hormone: challenges during early puberty - Ly, Helena-Jamin; Ankarberg-Lindgren, Carina; Fors, Hans; Nilsson, Staffan; Dahlgren, Jovanna (Frontiers in Endocrinology, 2025)
ObjectiveIt can be challenging to determine the correct dosage of recombinant growth hormone (GH) in children with GH deficiency, leading to highly variable treatment responses. Insulin-like growth factor-1 (IGF-1) is a tool for monitoring GH treatment and dosing. However, IGF-1 levels depend on sex, age, and pubertal stage, amongst other factors, making its interpretation somewhat difficult. This study aimed to evaluate descriptively a group of 93 children treated per protocol with GH to assess the influence of pubertal signs and sex steroid levels on the interpretation of IGF-1.Methods93 (67 boys and 26 girls) prepubertal children who participated in a previous GH treatment trial were included. Age, pubertal stage, weight, height, GH dose, and IGF-1 plasma concentrations were collected at least yearly from 2 years before pubertal start and 3 years after pubertal start. Levels of estradiol in girls and testosterone in boys were analyzed from previously collected frozen samples.ResultsNine of 58 (15.5%) estradiol samples in girls with Tanner breast stage 1 had pubertal levels of estradiol ≥25 pmol/L. For boys with testes size <4 mL, 24 out of the 153 (15.7%) testosterone samples were above the pubertal cut-off, ≥0.47 nmol/L. All the IGF-1 samples were divided into two groups based on an IGF-1 standard deviation score (SDS) of ≥2 or <2 SDS. The IGF-1 ≥2 SDS samples had a higher median (range) GH dose, 0.042 (0.02-0.10) mg/kg/day, compared with the IGF-1 <2 SDS samples, 0.038 (0.01-0.10) mg/kg/day, p<0.001. In the IGF-1 ≥2 SDS samples vs the IGF <2 SDS samples, estradiol levels were lower among girls, 13 (3-214) vs 102 (1-1070) pmol/L p<0.001, and testosterone levels were lower among boys, 0.35 (0.11-27.2) vs 6.9 (0.04-31.2) nmol/L p<0.001.ConclusionInterpretation of IGF-1 near puberty is challenging due to the influence of sex steroids. Variations in sex steroid levels and pubertal status can lead to misleading interpretations and an overestimation of IGF-1 SDS. Establishing an IGF-1 reference range that includes sex steroid levels can improve its clinical use to monitor GH treatment.